INOVASI PEMBELAJARAN MATEMATIKA: PENGEMBANGAN MODEL BERBASIS DIGITAL DENGAN PENDEKATAN DIFERENSIASI PADA SISWA KELAS X SMAN 7 DENPASAR - I Dewa Putu Juwana; I Komang Sukendra (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
This study aims to develop a digital-based mathematics learning model with a differentiation approach that suits the characteristics of tenth-grade students at SMAN 7 Denpasar. The study used a mixed methods approach, combining qualitative exploration through interviews, observations, and focus group discussions (FGDs) with teachers and education experts, as well as quantitative measurement through questionnaires to assess the model's effectiveness and acceptability. The results show that the developed model consists of four main components: digital data-based differentiation planning, adaptive learning implementation through an interactive platform, integrated digital assessment, and adaptive reflection and feedback. The implementation of this model increased student engagement, motivation, and mathematics learning outcomes by 12–18% compared to conventional learning, while simultaneously reducing mathematics learning anxiety. This model provides practical guidance for teachers in designing learning that is responsive to differences in student abilities and learning styles. The research findings confirm that digital integration and learning differentiation are strategic innovations for improving the quality of mathematics learning in the digital era and supporting the implementation of the Independent Curriculum.